SEARCH APPLICATIONS IN GOODS WITH METRO PACIFIC PLACE Using Macromedia Dreamweaver 8 - Adi Kristianto (Jurnal Sistem Informasi, 2008)
Along with the development of the age and the rapid technological and  recently, almost all layers of society in the world using a computer in  various fields of work. One of these items in a search process Dept. Store.  Goods Search application was used for the efficient time facilitate the search in the goods desired by the customer in the warehouse  storage of goods made with computer.  Making Application Search Metro Pacific Place Goods on this  using Macromedia Dreamweaver 8 app lication programs and for connect it using the PHP program.